Screen Time on School Days and Risks for Psychiatric Symptoms and Self-Harm in Mainland Chinese Adolescents - Liu, Mingli; Ming, Qingsen; Yi, Jinyao; Wang, Xiang; Yao, Shuqiao (Frontiers in Psychology, 2016)
Objective To investigate associations of television and of video game or non-educational computer use (VG/CU) exposure volumes in a typical school day with psychiatric symptoms and suicidal ideation/self-injurious behavior (self-harm), in mainland Chinese adolescents. Methods Secondary school pupils (N = 13,659; mean age: 15.18 ± 1.89) from 10 urban areas sampled from different regions of mainland China were recruited. The subjects were divided into the follow four screen exposure volume groups for television and VG/CU respectively based on a self-administered questionnaire: 0 h/d, >0 to ≤1 h/d, >1 to ≤2 h/d, and >2 h/d. Demographic and psychiatric symptoms were recorded for each respondent. Odds ratios (ORs) and 95% confidence intervals (CIs) for several types of psychological problems and self-harm were calculated. Results For television, >2 hours per school day was associated with greater risk of depression in both boys (OR = 1.33, 95%CI: 1.02–1.73) and girls (OR = 1.62, 95%CI: 1.19– 2.21), of anxiety in boys (OR = 1.43, 95%CI: 1.05–1.95), of general emotional, behavioral, and social problems (GEBSPs) in girls (OR = 1.55, 95%CI: 1.01–2.39), and of oppositional defiant problems (ODPs) in girls (OR = 1.65, 95% CI: 1.09–2.50), compared with the reference group. Conversely, television exposure of >0 to ≤1 hour per school day was associated with lower self-harm risk in boys (OR = 0.81, 95%CI: 0.67–0.99) compared with the no television exposure group. For VG/CU, higher risks of anxiety (OR = 1.40, 95%CI: 1.06–1.86) and of attention deficit/hyperactivity problems (ADHPs) (OR = 1.56, 95%CI: 1.02–2.38) were associated with excessive VG/CU time (>2 h per school day) in boys compared with the no VG/CU exposure group. Higher risks of self-harm and all other psychiatric problems (including anxiety and ADHPs in girls) were associated with any school-day VG/CU exposure, compared to no VG/CU exposure, in both genders. Conclusion For mainland Chinese secondary school students, associations of psychiatric problems and self-harm were much more strongly associated with exposure to VG/CU than with exposure to television. The findings suggest that VG/CU exposure on weekdays should be considered in psychiatric interventions for adolescents.